2005
DOI: 10.1016/j.acn.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Category and letter verbal fluency across the adult lifespan: relationship to EEG theta power

Abstract: The purpose of this study was to examine the impact of age, sex, and education on category and letter verbal fluency task performance. A secondary goal was to examine whether resting EEG theta power in bilateral frontal and temporal lobes impacts age-associated decline in verbal fluency task performance. A large sample (N = 471) of healthy, normal participants, age 21-82, was assessed for letter fluency (i.e., FAS), and for category fluency (i.e., Animal Naming), and with a 32-channel EEG system for 'eyes-open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
109
1
18

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(142 citation statements)
references
References 48 publications
14
109
1
18
Order By: Relevance
“…Previous studies have suggested separate neural substrates underlying these phonemically vs semantically based types of performance (Billingsley et al, 2004;Brickman et al, 2005). Healthy participants have been found to score higher on the category-cued test (Brickman et al, 2005), suggesting that this measure may be easier than the letter-cued test. Thus, it is possible that ET did not significantly improve category-cued performance because of a difficulty effect.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have suggested separate neural substrates underlying these phonemically vs semantically based types of performance (Billingsley et al, 2004;Brickman et al, 2005). Healthy participants have been found to score higher on the category-cued test (Brickman et al, 2005), suggesting that this measure may be easier than the letter-cued test. Thus, it is possible that ET did not significantly improve category-cued performance because of a difficulty effect.…”
Section: Discussionmentioning
confidence: 93%
“…This is a sensitive task for frontal lobe functions (Alvarez and Emory, 2006) and hence to frontotemporal dementia, whereas category fluency is a marker of semantic memory breakdown typical in AD (e.g., Mathuranath et al, 2000). Phonemic verbal fluency is considered valuable in detecting cognitive alterations in the aged given its stability throughout the ageing process (Brickman et al, 2005), which may offer diagnostic utility in the assessment of older drivers. However, it is important to note that one item from the ACE-R does not tell the whole "story" about driving ability, as visuospatial abilities and visual attention (modalities not examined in the ACE-R) are also crucial for safe driving (Reger et al, 2004;Mathias and Lucas, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Their fMRI study revealed a bilateral activation of the frontal lobes in this task, with a predominance of LH. The involvement of both cerebral hemispheres has as well been verified by Brickman et al (2005) in their EEG study. In the processing of lexical orthographic retrieval and lexical semantic retrieval tasks (retrieval of words belonging to the same semantic field, for instance, animals), activation of bilateral frontal and temporal regions was recorded.…”
Section: Lexical-semantic Processingmentioning
confidence: 95%